Advancements in 2D flexible nanoelectronics: from material perspectives to RF applications. (23rd October 2017) - Zhu, Weinan; Park, Saungeun; Yogeesh, Maruthi N; Akinwande, Deji
Abstract: In the past decade, two-dimensional (2D) atomic crystals have stimulated great interest in the electronic device community for their interesting physics and diverse applications. With the rapid growing market of wearable electronics and the internet of things, flexible nanoelectronics with high operation speed and low power consumption has become one of the most researched topics. In this regard, 2D atomic van der Waals crystals have emerged as promising candidates for such applications owing to their compelling capabilities including ultimate thickness scalability, superior mechanical flexibility and highly tunable electronic performance. In this review, state-of-the-art advancements in 2D flextronics based on chemical vapor deposition (CVD) monolayer graphene, CVD monolayer molybdenum disulphide (MoS2 ) and exfoliated few layer black phosphorus are presented with specific emphasis on radio frequency applications.